Wedding Dress (1943) between Adolphe Appia's active and passive light: an analysis methodology (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This article analyzes some scenes from the play Wedding Dress, text by Nelson Rodrigues (1912-1980), with the eyes turned to its lighting, in order to perceive the activity of light in the expression of spaces (environments) through the contrast between light and shadow. To this end, the Swiss Adolphe Appia's (1862-1928) concepts of active light and passive light are methodologically used to analyze the stage lighting plan and the original lighting operation script for the play debut in December 1943, discovered in the collection of João Angelo Labanca (1913-1988) and available at the Documentation Center of the National Art Foundation.
Keywords: Adolphe Appia; Wedding Dress; light and shadow